The Relationship Between Workload and Fatigue and Work Productivity at PT. PLN Nusantara Power Up Tarahan - Puteri Gold Regina, Sheren; adinda (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Workload and fatigue are important factors affecting productivity. PT. PLN NP UP Tarahan experienced a high workload of 70%, with fatigue at 50%, and productivity in 2022-2023 decreased by 77% due to high workload and fatigue among workers in the WTP, BTG, CAH, Cleaning Service, and Cleaning Admin areas. The objective of this study was to determine the relationship between workload and fatigue on work productivity at PT. PLN NP UP Tarahan in 2024. This study used a quantitative cross-sectional design. The study population was 401 workers. The study was conducted at PT. PLN NP UP Tarahan, with a sample of 78 respondents using purposive sampling and data collection through interviews using a questionnaire from July 13 to July 16, 2024. Data were analyzed using univariate and bivariate chi-square methods. The study results indicate a relationship between workload and work productivity at PT PLN NP UP Tarahan, with a p-value of 0.007 and an OR of 0.266. Work Fatigue and Work Productivity were correlated with a p-value of 0.007 and an OR of 0.274. PT PLN NP UP Tarahan is expected to adjust the division of tasks or workload to physical abilities and work capacity.